A Study on CIGS Thin-Film Solar Cells Through SCAPS-1D Simulations - Rehman, Ateeq ul; Afzal, Shahbaz; Iqra Naeem; Munir, Tahir; Sakhi Ghulam Sarwar; Saleem, Muhammad; Obodo, Raphael Mmaduka (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2025)
This research utilized SCAPS-1D simulation software to model a high-efficiency CIGS-based solar cell with configuration Ag/ZnO:Al/i-ZnO/CdS/CIGS/Mo. Various optimizations were performed, focusing on the absorber layer’s thickness, acceptor density, and defect density to enhance the cell’s performance. Furthermore, the work function values of rear contact metals were analyzed to understand their influence on critical photovoltaic parameters like open-circuit voltage (Voc), short-circuit current (Jsc), fill factor (FF), and power conversion efficiency (PCE). The impact of temperature was also analyzed, emphasizing the necessity of effective thermal management techniques to promise consistent and effective performance under varying environmental conditions. The study further emphasized the importance of the hole transport layer (HTL) in improving charge carrier collection and reducing recombination losses. Efforts to develop cadmium-free designs reinforced the push towards sustainable and eco-friendly photovoltaic technologies. The optimal parameters achieved in this study included an absorber layer thickness of 0.4 µm, acceptor density of absorber at 1×1018 cm−3, defect density of 1×1015 cm−3, and a back contact selenium work function of 5.9 eV. Under AM 1.5 G spectrum illumination at 300 K, the optimized cell demonstrated exceptional performance, with a Voc of 0.7338 V, Jsc of 36.352805 mA/cm2, FF of 83.33%, and PCE of 22.23%. The results were benchmarked against existing literature, showcasing significant improvements in device efficiency. This study provides a comprehensive framework for optimizing CIGS-based solar cells and highlights their potential for delivering high-performance, sustainable solar energy.